Análisis comparativo de los modelos de medición para el capital intelectual (2020)
The following writing refers to the models of measurement of Intellectual Capital, showing the result of the research work, responding to the problematic question of why it is necessary to measure Intellectual Capital and thus describe the benefits of implementing any of the models in the companies, but first it was necessary to describe the concept of Intellectual Capital and define what its components or elements are, followed by observing the modification of measurement models over time and the use that has been given to this wonderful tool, thus proceeding to perform an analysis among the most relevant measurement models, taking into account their authors, their bases and final results for the entities in which they are applied or developed; thus proceed to give answers to the hypotheses made at the beginning of the research work and finally expose the research conclusions